How Well Can Online GPS PPP Post-processing Services be Used to Establish Geodetic Survey Control Networks? - Ebner, R.; Featherstone, Will (Walter de Gruyter, 2008)
Establishing geodetic control networks for subsequent surveys can be a costly business, even when using GPS. Multiple stations should be occupied simultaneously and post-processed with scientific software. However, the free availability of online GPS precise point positioning (PPP) post-processing services offer the opportunity to establish a whole geodetic control network with just one dual-frequency receiver and one field crew. To test this idea, we compared coordinates from a moderate-sized (~550 km by ~440 km) geodetic network of 46 points over part of south-western Western Australia, which were processed both with the Bernese v5 scientific software and with the CSRS (Canadian Spatial Reference System) PPP free online service. After rejection of five stations where the antenna type was not recognised by CSRS, the PPP solutions agreed on average with the Bernese solutions to 3.3 mm in east, 4.8 mm in north and 11.8 mm in height.The average standard deviations of the Bernese solutions were 1.0 mm in east, 1.2 mm in north and 6.2 mm in height, whereas for CSRS they were 3.9 mm in east, 1.9 mm in north and 7.8 mm in height, reflecting the inherently lower precision of PPP. However, at the 99% confidence level, only one CSRS solution was statistically different to the Bernese solution in the north component, due to a data interruption at that site. Nevertheless, PPP can still be used to establish geodetic survey control, albeit with a slightly lower quality because of the larger standard deviations. This approach may be of particular benefit in developing countries or remote regions, where geodetic infrastructure is sparse and would not normally be established without this approach.